The impact of the COVID-19 epidemic on tuberculosis control in China - Fei, Huang; Yinyin, Xia; Hui, Chen; Ni, Wang; Xin, Du; Wei, Chen; Tao, Li; Shitong, Huan; Miaomiao, Sun; Mingting, Chen; Keshavjee, Salmaan; Yanlin, Zhao; et al. (The Lancet regional health. Western Pacific, 2020)
In response to the COVID-19 epidemic, China implemented a series of interventions that impacted tuberculosis (TB) control in the country. Based on routine surveillance data and questionnaires, the study analyzed TB notification, follow-up examinations, and treatment outcomes. The data were split into three phases in relation to outbreak, lockdown and reopen when the nationwide COVID-19 response started in 2020: control (11 weeks prior), intensive (11 weeks during and immediately after), and regular (4 additional weeks). Data from 2017–2019 were used as baseline. The notified number of TB patients decreased sharply in the 1st week of the intensive period but took significantly longer to rebound in 2020 compared with baseline. The percentages of TB patients undergoing sputum examination within one week after 2 months treatment and full treatment course in the intensive period were most affected and decreased by 8% in comparison with control period. 75•2% (221/294) of counties reallocated CDC and primary health care workers to fight the COVID-19 epidemic, 26•9% (725/2694) of TB patients had postponed or missed their follow-up examinations due to travel restrictions and fear of contracting COVID-19. In the short term, the COVID-19 epidemic mostly affected TB notification and follow-up examinations in China, which may lead to a surge of demand for TB services in the near future. To cope with this future challenge, an emergency response mechanism for TB should be established. National Health Commission of China–Bill & Melinda Gates Foundation TB Collaboration project (OPP1137180).